Eco-Friendly Synthesis and Characterization of Double-Crossed Link 3D Graphene Oxide Functionalized With Chitosan for Adsorption of Sulfamethazine From Aqueous Solution: Experimental and DFT Calculations - Hamed, Rinad; Jodeh, Shehdeh; Hanbali, Ghadir; Safi, Zaki; Berisha, Avni; Xhaxhiu, Kledi; Dagdag, Omar (Frontiers in Environmental Science, 2022)
Graphene oxide–chitosan composites are attracting considerable interest as an eco-friendly adsorbent material for most aquatic environmental pollutants. Today, the focus is on the emerging applications of 2D and 3D graphene functionalized with chitosan to enhance its mechanical properties and adsorption efficiency. Herein, the super adsorbent 3D graphene functionalized with chitosan (3D GF-CS) is synthesized to remove sulfamethazine, (SMZ) as a model aquatic antibiotic pharmaceutical. The synthesized materials were characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), X-ray photon spectroscopy (XPS), Brunauer–Emmett–Teller (BET), and Raman spectroscopy. After that, adsorption experiments were conducted for SMZ adsorption to find out the optimized adsorption parameters, such as pH, temperature, contact time, initial antibiotic concentration, and adsorbent dosage. The results show the optimal adsorption parameters were as pH of 7, temperature of 25°C, initial antibiotic concentration Ci of 50 ppm. Also, the kinetics, isotherms models, and thermodynamics parameters of SMZ adsorption were studied. The experimental results revealed to be best suited by both the pseudo-second-order kinetic and the Freundlich isotherm model compared with other isotherm models. The thermodynamics parameters demonstrated that the adsorption is exothermic, exhibiting higher adsorption efficiency at lower temperature. In addition, Gibb’s free energy suggested the adsorption to be spontaneous as well as entropy indication of the loss of disorder. Furthermore, the regeneration of 3D GF-CS was utilized in ten consecutive cycles, and the SMZ adsorption capacity did not decline significantly. Additionally, this research studied the adsorption energies and how sulfamethazine adsorbs onto 3D GF-CS was determined by applying the density-functional–based tight binding (DFTB) and Monte Carlo simulations at different adsorption positions. The chemical reactivity (local and global) of the free drug was investigated using the density functional theory (DFT), namely, the B3LYP and PBEPBE functionals with the 6–31+G (d, p) basis set in the gas phase and aqueous solution.